Wawasan 2020 - Kamarudin Jaffar, 1951-; Hazami Habib; Institut Kajian Dasar Malaysia (Kuala Lumpur : Institut Kajian Dasar, 1993)
Concept of Malaysia's future in the 2020s; papers of seminars.
In Malay.
Includes bibliographical references.
Keywords: Economic forecasting -- Malaysia; Malaysia -- Economic policy; Malaysia -- Politics and government